2011
DOI: 10.1016/j.theriogenology.2010.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Fetal calf serum enhances in vitro production of Bos taurus indicus embryos

Abstract: The objective of this study was to determine the effect of fetal calf serum (FCS) on the quality of in vitro produced bovine embryos. Cumulus oocyte-complexes (COCs, n = 2 449) recovered by ovum pick-up from Bos taurus indicus donors were randomly assigned to experimental groups. Sperm selected by Percoll gradient was used for in vitro fertilization (insemination = Day 0). In Experiment 1 (n = 1 745 COCs), zygotes were cultured in vitro in Synthetic Oviduct Fluid + 4 mg/mL of bovine serum albumin (BSA), or BSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
2
15
0
1
Order By: Relevance
“…The use of fetal bovine serum in culture media has been controversial with both positive and negative effects reported. Several studies have demonstrated increased blastocyst development when FBS is supplemented, (Lazzari et al 2002, Leivas et al 2011) similar to the current study. However, the use of FBS has also been associated with abnormal fetal growth, in subsequent pregnancies (Young et al 1998, Lazzari et al 2002, Farin et al 2004).…”
Section: Immunofluorescene Of H3r26me2 During In Vitro Developmentsupporting
confidence: 88%
See 3 more Smart Citations
“…The use of fetal bovine serum in culture media has been controversial with both positive and negative effects reported. Several studies have demonstrated increased blastocyst development when FBS is supplemented, (Lazzari et al 2002, Leivas et al 2011) similar to the current study. However, the use of FBS has also been associated with abnormal fetal growth, in subsequent pregnancies (Young et al 1998, Lazzari et al 2002, Farin et al 2004).…”
Section: Immunofluorescene Of H3r26me2 During In Vitro Developmentsupporting
confidence: 88%
“…In addition, FBS has an adverse effect on embryo survival after cryopreservation, due to increased lipid content within the embryos ). Leivas and co-authors (Leivas et al 2011) also suggest that embryos from certain breeds of cattle may depend more on the presence of FBS in the culture media. Similar to the current study, they report a 10% increase in blastocyst rates between IVP embryos from Bos indicus cattle cultured with 2% FBS than embryos cultured with BSA alone (Leivas et al 2011).…”
Section: Immunofluorescene Of H3r26me2 During In Vitro Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Culture media containing FBS generally produce better blastocyst rates because of the presence of growth factors and other known and unknown components that the growing embryo requires [6,7], although early embryo development may be delayed [8,9]. Although many laboratories in the world have tried to remove FBS from their culture media, the addition of FBS is still a common practice in many countries, such as Brazil, the biggest producer of bovine IVP embryos.…”
Section: Introductionmentioning
confidence: 99%